The Relationship between Mother's Knowledge Level and Antibiotic Use Behavior in Toddlers Age 0-2 Years At Dewantara Health Center, North Aceh Regency - Anita Syafridah (AVERROUS: Jurnal Kedokteran dan Kesehatan Malikussaleh, 2022)
Antibiotics are chemical substances derived from bacteria and fungi that have the function to kill or inhibit the growth of pathogens which are generally used for the treatment of diseases caused by bacteria and the use of antibiotics must be used appropriately and according to indications. The purpose of this study was to determine the relationship between the mother's level of knowledge and the behavior of using antibiotics. This research is an analytic study with a cross sectional approach. Sampling was done by purposive sampling method. The measuring instrument used is a questionnaire. Data analysis was carried out by Spearman analysis. The study was conducted at the Dewantara Community Health Center with a sample of 72 people. The results showed that the level of knowledge of respondents in the good knowledge category was 31.9%, the sufficient category was 48.6%, and the less category was 19.4%. The good behavior category is 26.4%, the sufficient category is 51.4%, and the less category is 22.2%. The results of the Chi-square test obtained a significance value of 0.001. The results of this study indicate that there is a relationship between the mother's level of knowledge and the behavior of using antibiotics in children aged 0-2 years at the Dewantara Public Health Center, North Aceh Regency